THE IMPACT ANALYSIS ON THE CONDUCTOR'S DISTANCE BETWEEN THE CONDUCTORS AND THE DEPTH OF THE IEEE-ROD-BASED GROUND SYSTEM STD 80 – 2000 - Meike Alif Latifah (Fakultas Teknik Elektro - Universitas Sultan Ageng Tirtayasa, 2019)
The phase-to-ground disruption of the extra high Voltage Master's line (GITET) of 500 kV caused a surge of tension to the ground.The interruption flow will flow on the metal parts of the equipment and to the destruction tool.It will create a voltage gradient between the equipment with the equipment, the equipment with soil and gradients with the ground surface itself that is harmful to the human safety in the Switchyard area. Keywords: Grid-rod grounding system, Depth, 500 KV GITET